2017
DOI: 10.4317/jced.53450
|View full text |Cite
|
Sign up to set email alerts
|

Elongated styloid process evaluation on digital panoramic radiograph in a North Italian population

Abstract: BackgroundThe aim of this study is to evaluate the prevalence of elongated styloid process in digital panoramic radiographs in a North Italian population in relation to age, gender and side.Material and MethodsThis study was performed as a retrospective analysis on digital panoramic radiographs of 600 (271 males and 329 females) Italian patients between 6 and 87 years old. The styloid process length were measured using the measuring tool of Sidexis Software. It was measured from the point where it left the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 19 publications
3
35
0
3
Order By: Relevance
“…Since this clinical situation can be associated with pain, it should be considered when a differential diagnosis is made. According to the majority of research, the prevalence of elongation increases in older individuals [10][11][12]. This phenomenon could be caused by degeneration of the ligamentous complex, and a generalized tendency for deposition of calcium salts, related with age [5].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since this clinical situation can be associated with pain, it should be considered when a differential diagnosis is made. According to the majority of research, the prevalence of elongation increases in older individuals [10][11][12]. This phenomenon could be caused by degeneration of the ligamentous complex, and a generalized tendency for deposition of calcium salts, related with age [5].…”
Section: Discussionmentioning
confidence: 99%
“…The panoramic radiograph is a valuable and reliable tool for the styloid process length analysis, not only in qualitative but also in a quantitative way [13,23]. Additionally, it is considered a routine exam taken in almost every dental practice, as it is easy to collect; it eliminates the styloid process overlapping issue that frequently occurs in cephalograms and it has a much lower radiation dose and lower cost than CT or CBCT, which are considered the gold standard for diagnosis of the elongated styloid process [6,12,23]. The demographic data in the present research was similar to those reported in previous articles; women seek orthodontic treatment more frequently than men, and most patients have skeletal class I and a mesofacial pattern [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations